Electronic Effects in Carbene‐Mediated CH Bond Functionalization: An Experimental and Theoretical Study. Issue 11 (17th March 2014) - Boultadakis‐Arapinis, Mélissa; Gandon, Vincent; Prost, Elise; Micouin, Laurent; Lecourt, Thomas
Abstract In this article, we show that short‐distance and long‐range electronic effects are strongly affecting the mechanism and stereoselectivity of Rh(II)‐carbene mediated CH functionalization processes. Based on experimental studies with deuterium‐labelled carbohydrates and DFT calculations, we show that the orientation of the lone pairs of adjacent heteroatoms, as well as the nature of substituents located far from the reaction center, are inducing a shift from the classical concerted mechanism to the less common stepwise process. Furthermore, we reveal that the stereochemical outcome of these transformations is depending on the relative energies of the CH bond activation and Rh(II)‐carbene isomerization barriers. The formation of a single diastereoisomer is thus resulting from Curtin–Hammet‐like kinetics when insertion occurs in poorly activated CH bonds. However, the formation of diastereoisomeric mixtures is resulting from two disconnected and totally stereoselective transformations when the reactivity of the CH bonds towards electrophilic metallocarbenes is increased by short‐distance or long‐range electronic effects. Abbreviations: Rh: rhodium; Bn: benzyl; Bz: benzoyl; Me: methyl; t‐Bu: tert‐butyl; Ph: phenyl; Ac: acetyl; ClAc: chloroacetyl; TBDMS: tert‐butyldimethylsilyl; TMS: trimethylsilyl; D: deuterium; P: protecting group; L: ligand; THF: tetrahydrofuran; DFT: density functional theory; TS: transition state; BO: bond order; NMR: nuclear magnetic resonance; MS: mass spectrometry; NOE: nuclear Overhauser effect. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>